2011
DOI: 10.1002/anie.201101909
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of Chiral Periodic Organosilica Materials with Ultrasmall Mesopores

Abstract: Helical organosilica materials were synthesized for the first time using a novel binaphthyl-based chiral co-monomer in less than 1 hour. The incorporation of a chiral co-monomer in the wall was shown to influence the curvature of the helical materials. As the amount of the chiral co-monomer was increased, the degree of curvature increased, illustrating the importance of this monomer to the overall morphology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 64 publications
1
21
0
Order By: Relevance
“…Chiral mesoporous silica and organosilica materials are now well known . Forming mesoporous solids with chiral nematic (cholesteric) order is attractive since these structures could have photonic properties that arise from their order.…”
Section: Methodsmentioning
confidence: 99%
“…Chiral mesoporous silica and organosilica materials are now well known . Forming mesoporous solids with chiral nematic (cholesteric) order is attractive since these structures could have photonic properties that arise from their order.…”
Section: Methodsmentioning
confidence: 99%
“…2 The incorporation of organic segments within the walls of PMO materials also provides the opportunity to create materials with macroscopic chirality by using chiral organosilsesquioxane monomers. 3 Hence, the development of chiral PMO materials has been of significant interest given their potential impact in heterogeneous asymmetric catalysis, chiral chromatography and non-linear optics. Early examples of chiral PMO syntheses in which the chiral structure is incorporated into the PMO backbone required the addition of large quantities of silica precursor such as Si(OEt) 4 (TEOS) in addition to the chiral organosilsesquioxane monomer in order to obtain materials with any degree of order or porosity.…”
Section: Introductionmentioning
confidence: 99%
“…Early examples of chiral PMO syntheses in which the chiral structure is incorporated into the PMO backbone required the addition of large quantities of silica precursor such as Si(OEt) 4 (TEOS) in addition to the chiral organosilsesquioxane monomer in order to obtain materials with any degree of order or porosity. [4][5][6][7][8] More recently, efforts have focused on the templated co-condensation of chiral and achiral organosilsesquioxane monomers, 3,[9][10][11] or the selfcondensation of purely chiral organosilsesquioxane monomers in order to obtain chiral PMO materials with a higher chiral content than that normally achieved with TEOS-based chiral PMOs. [12][13][14][15][16][17] We recently designed chiral PMOs based on a new chiral amplification strategy in which two complementary organosilsesquioxane monomers are co-condensed: one is a chiral monomer acting as a 'dopant' and the other is an achiral 'bulk' monomer with a structure that enables an efficient transfer of chirality from the dopant through the bulk of the PMO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). [2][3][4] Although amorphous materials can be prepared without the benefit of a sacrificial template and still have high surface areas, pore structures can be expected to be significantly disordered, burying active sites inside the wall and decreasing permeation of substrates. 5 On the other hand, surfactant-templated synthetic methods permit greater control over morphology and porosity, with the ultimate example being the 2002 report by Inagaki and co-workers who showed that a biphenylene-bridged (2) periodic mesoporous organosilica (PMO) materials could be prepared that displayed molecular scale order in the walls.…”
mentioning
confidence: 99%